Analisis E-Bisnis Terhadap Amazon dan Aquarelle - Tanuar, Evawaty; Yosanny, Agustinna (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The internet and digital world is one thing that needs to be taken into account by the Company. Business through Internet, known as e-business, is another way to increase the relation between company and customers or prospective customers. Analysis from the view point of customers and the integration of technologies was conducted on 2 examples sites that well known in doing online business but have different history on how it started the e-commerce. They are Amazon and Aquarelle. By comparing the two sites, the characteristics of e-commerce sites could be studied. As a result, there are striking differences between these two sites, where Amazon is more oriented to sales, while Aquarelle more on customer-oriented impact to the design and implementation of their e-business.